1983
DOI: 10.1093/bja/55.8.729
|View full text |Cite
|
Sign up to set email alerts
|

Suxamethonium: A New Look at Pretreatment

Abstract: Fifty patients were pretreated with either suxamethonium 10 mg or gallamine 20 mg before an injection of suxamethonium 1 mg kg-1. The effect of the pretreatment upon neuromuscular transmission was monitored by recording the mechanical response of the adductor pollicis muscle to indirect stimulation, using a 2-Hz train-of-four stimulus repeated every 12 s. The pretreatment injection of suxamethonium caused fasciculation in one-quarter of the patients studied. Significant neuromuscular blockade occurred during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In practice, this aim was not entirely realized. As reported by previous authors [5,6,9,10], a variable proportion of patients develop fasciculations after pretreatment ("selftaming") with suxamethonium. In the present study, this phenomenon was observed in two patients; it was not considered to invalidate the results of the investigation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In practice, this aim was not entirely realized. As reported by previous authors [5,6,9,10], a variable proportion of patients develop fasciculations after pretreatment ("selftaming") with suxamethonium. In the present study, this phenomenon was observed in two patients; it was not considered to invalidate the results of the investigation.…”
Section: Discussionsupporting
confidence: 61%
“…Sixty identical 1.1-ml ampoules containing 0.9% saline, suxamethonium 10 mg ml" 1 , gallamine 20 mg ml~l or pancuronium 1 mg ml" 1 were prepared by the Pharmacy Manufacturing Department of the Royal Liverpool Hospital. Similar doses of suxamethonium and gallamine have been used in many previous studies [5][6][7]. The doses of pancuronium 1 mg and gallamine 20 mg were considered to have equipotent effects on neuromuscular transmission.…”
Section: Methodsmentioning
confidence: 99%